Linked (Open) Data - Bibliographische Daten im Semantic Web - Danowski, Patrick; Goldfarb, Doron; Schaffner, Verena; Seidler, Wolfram (VÖB Mitteilungen)
Linked (Open) Data - bibliographic data on the Semantic Web. Report of the Working Group on Linked Data to the plenary assembly of the Austrian Library Network (translation of the title). Linked Data stands for a certain approach to publishing data on the Web. The underlying idea is to harmonise heterogeneous data sources of different origin in order to improve their accessibility and interoperability, effectively making them queryable as a big distributed database. This report summarises relevant developments in Europe as well as the Linked Data Working Group‘s strategic and technical considerations regarding the publishing of the Austrian Library Network’s (OBV’s) bibliographic datasets. It concludes with the mutual agreement that the implementation of Linked Data principles within the OBV can only be taken into consideration accompanied by a discussion about the provision of the datasets under a free license.

Digital signatures with minimal overhead from indifferentiable random invertible functions - Kiltz, Eike; Pietrzak, Krzysztof Z; Szegedy, Mario
In a digital signature scheme with message recovery, rather than transmitting the message m and its signature σ, a single enhanced signature τ is transmitted. The verifier is able to recover m from τ and at the same time verify its authenticity. The two most important parameters of such a scheme are its security and overhead |τ| − |m|. A simple argument shows that for any scheme with “n bits security” |τ| − |m| ≥ n, i.e., the overhead is lower bounded by the security parameter n. Currently, the best known constructions in the random oracle model are far from this lower bound requiring an overhead of n + logq h , where q h is the number of queries to the random oracle. In this paper we give a construction which basically matches the n bit lower bound. We propose a simple digital signature scheme with n + o(logq h ) bits overhead, where q h denotes the number of random oracle queries. Our construction works in two steps. First, we propose a signature scheme with message recovery having optimal overhead in a new ideal model, the random invertible function model. Second, we show that a four-round Feistel network with random oracles as round functions is tightly “public-indifferentiable” from a random invertible function. At the core of our indifferentiability proof is an almost tight upper bound for the expected number of edges of the densest “small” subgraph of a random Cayley graph, which may be of independent interest.

Learning with rounding, revisited: New reduction properties and applications - Alwen, Joel F; Krenn, Stephan; Pietrzak, Krzysztof Z; Wichs, Daniel
The learning with rounding (LWR) problem, introduced by Banerjee, Peikert and Rosen at EUROCRYPT ’12, is a variant of learning with errors (LWE), where one replaces random errors with deterministic rounding. The LWR problem was shown to be as hard as LWE for a setting of parameters where the modulus and modulus-to-error ratio are super-polynomial. In this work we resolve the main open problem and give a new reduction that works for a larger range of parameters, allowing for a polynomial modulus and modulus-to-error ratio. In particular, a smaller modulus gives us greater efficiency, and a smaller modulus-to-error ratio gives us greater security, which now follows from the worst-case hardness of GapSVP with polynomial (rather than super-polynomial) approximation factors. As a tool in the reduction, we show that there is a “lossy mode” for the LWR problem, in which LWR samples only reveal partial information about the secret. This property gives us several interesting new applications, including a proof that LWR remains secure with weakly random secrets of sufficient min-entropy, and very simple constructions of deterministic encryption, lossy trapdoor functions and reusable extractors. Our approach is inspired by a technique of Goldwasser et al. from ICS ’10, which implicitly showed the existence of a “lossy mode” for LWE. By refining this technique, we also improve on the parameters of that work to only requiring a polynomial (instead of super-polynomial) modulus and modulus-to-error ratio.

Efficient signatures of knowledge and DAA in the standard model - Bernhard, David; Fuchsbauer, Georg; Ghadafi, Essam
Direct Anonymous Attestation (DAA) is one of the most complex cryptographic protocols deployed in practice. It allows an embedded secure processor known as a Trusted Platform Module (TPM) to attest to the configuration of its host computer without violating the owner’s privacy. DAA has been standardized by the Trusted Computing Group and ISO/IEC. The security of the DAA standard and all existing schemes is analyzed in the random-oracle model. We provide the first constructions of DAA in the standard model, that is, without relying on random oracles. Our constructions use new building blocks, including the first efficient signatures of knowledge in the standard model, which have many applications beyond DAA.

Neural development is dependent on the function of specificity protein 2 in cell cycle progression - Liang, Huixuan; Xiao, Guanxi; Yin, Haifeng; Hippenmeyer, Simon; Horowitz, Jonathan; Ghashghaei, Troy (Development)
Faithful progression through the cell cycle is crucial to the maintenance and developmental potential of stem cells. Here, we demonstrate that neural stem cells (NSCs) and intermediate neural progenitor cells (NPCs) employ a zinc-finger transcription factor specificity protein 2 (Sp2) as a cell cycle regulator in two temporally and spatially distinct progenitor domains. Differential conditional deletion of Sp2 in early embryonic cerebral cortical progenitors, and perinatal olfactory bulb progenitors disrupted transitions through G1, G2 and M phases, whereas DNA synthesis appeared intact. Cell-autonomous function of Sp2 was identified by deletion of Sp2 using mosaic analysis with double markers, which clearly established that conditional Sp2-null NSCs and NPCs are M phase arrested in vivo. Importantly, conditional deletion of Sp2 led to a decline in the generation of NPCs and neurons in the developing and postnatal brains. Our findings implicate Sp2-dependent mechanisms as novel regulators of cell cycle progression, the absence of which disrupts neurogenesis in the embryonic and postnatal brain.

Optimal Coalition Structures in Cooperative Graph Games - Bachrach, Yoram; Kohli, Pushmeet; Kolmogorov, Vladimir; Zadimoghaddam, Morteza
Representation languages for coalitional games are a key research area in algorithmic game theory. There is an inher- ent tradeoff between how general a language is, allowing it to capture more elaborate games, and how hard it is computationally to optimize and solve such games. One prominent such language is the simple yet expressive Weighted Graph Games (WGGs) representation (Deng and Papadimitriou 1994), which maintains knowledge about synergies between agents in the form of an edge weighted graph. We consider the problem of finding the optimal coalition structure in WGGs. The agents in such games are vertices in a graph, and the value of a coalition is the sum of the weights of the edges present between coalition members. The optimal coalition structure is a partition of the agents to coalitions, that maximizes the sum of utilities obtained by the coalitions. We show that finding the optimal coalition structure is not only hard for general graphs, but is also intractable for restricted families such as planar graphs which are amenable for many other combinatorial problems. We then provide algorithms with constant factor approximations for planar, minorfree and bounded degree graphs.

Inference algorithms for pattern-based CRFs on sequence data - Takhanov, Rustem; Kolmogorov, Vladimir (ICML'13 Proceedings of the 30th International Conference on International)
We consider Conditional Random Fields (CRFs) with pattern-based potentials defined on a chain. In this model the energy of a string (labeling) x1...xn is the sum of terms over intervals [i,j] where each term is non-zero only if the substring xi...xj equals a prespecified pattern α. Such CRFs can be naturally applied to many sequence tagging problems. We present efficient algorithms for the three standard inference tasks in a CRF, namely computing (i) the partition function, (ii) marginals, and (iii) computing the MAP. Their complexities are respectively O(nL), O(nLℓmax) and O(nLmin{|D|,log(ℓmax+1)}) where L is the combined length of input patterns, ℓmax is the maximum length of a pattern, and D is the input alphabet. This improves on the previous algorithms of (Ye et al., 2009) whose complexities are respectively O(nL|D|), O(n|Γ|L2ℓ2max) and O(nL|D|), where |Γ| is the number of input patterns. In addition, we give an efficient algorithm for sampling. Finally, we consider the case of non-positive weights. (Komodakis & Paragios, 2009) gave an O(nL) algorithm for computing the MAP. We present a modification that has the same worst-case complexity but can beat it in the best case.

Reweighted message passing revisited - Kolmogorov, Vladimir
We propose a new family of message passing techniques for MAP estimation in graphical models which we call Sequential Reweighted Message Passing (SRMP). Special cases include well-known techniques such as Min-Sum Diusion (MSD) and a faster Sequential Tree-Reweighted Message Passing (TRW-S). Importantly, our derivation is simpler than the original derivation of TRW-S, and does not involve a decomposition into trees. This allows easy generalizations. We present such a generalization for the case of higher-order graphical models, and test it on several real-world problems with promising results.

Proofs of Space - Dziembowski, Stefan; Faust, Sebastian; Kolmogorov, Vladimir; Pietrzak, Krzysztof Z
Proofs of work (PoW) have been suggested by Dwork and Naor (Crypto'92) as protection to a shared resource. The basic idea is to ask the service requestor to dedicate some non-trivial amount of computational work to every request. The original applications included prevention of spam and protection against denial of service attacks. More recently, PoWs have been used to prevent double spending in the Bitcoin digital currency system. In this work, we put forward an alternative concept for PoWs -- so-called proofs of space (PoS), where a service requestor must dedicate a significant amount of disk space as opposed to computation. We construct secure PoS schemes in the random oracle model, using graphs with high "pebbling complexity" and Merkle hash-trees.

Potts model, parametric maxflow and k-submodular functions - Gridchyn, Igor; Kolmogorov, Vladimir
The problem of minimizing the Potts energy function frequently occurs in computer vision applications. One way to tackle this NP-hard problem was proposed by Kovtun [19, 20]. It identifies a part of an optimal solution by running k maxflow computations, where k is the number of labels. The number of “labeled” pixels can be significant in some applications, e.g. 50-93% in our tests for stereo. We show how to reduce the runtime to O (log k) maxflow computations (or one parametric maxflow computation). Furthermore, the output of our algorithm allows to speed-up the subsequent alpha expansion for the unlabeled part, or can be used as it is for time-critical applications. To derive our technique, we generalize the algorithm of Felzenszwalb et al. [7] for Tree Metrics . We also show a connection to k-submodular functions from combinatorial optimization, and discuss k-submodular relaxations for general energy functions.

Transformation of stimulus correlations by the retina - Simmons, Kristina; Prentice, Jason; Tkacik, Gasper; Homann, Jan; Yee, Heather; Palmer, Stephanie; Nelson, Philip; Balasubramanian, Vijay (PLoS Computational Biology)
Redundancies and correlations in the responses of sensory neurons may seem to waste neural resources, but they can also carry cues about structured stimuli and may help the brain to correct for response errors. To investigate the effect of stimulus structure on redundancy in retina, we measured simultaneous responses from populations of retinal ganglion cells presented with natural and artificial stimuli that varied greatly in correlation structure; these stimuli and recordings are publicly available online. Responding to spatio-temporally structured stimuli such as natural movies, pairs of ganglion cells were modestly more correlated than in response to white noise checkerboards, but they were much less correlated than predicted by a non-adapting functional model of retinal response. Meanwhile, responding to stimuli with purely spatial correlations, pairs of ganglion cells showed increased correlations consistent with a static, non-adapting receptive field and nonlinearity. We found that in response to spatio-temporally correlated stimuli, ganglion cells had faster temporal kernels and tended to have stronger surrounds. These properties of individual cells, along with gain changes that opposed changes in effective contrast at the ganglion cell input, largely explained the pattern of pairwise correlations across stimuli where receptive field measurements were possible.

Looking at mean-payoff and total-payoff through windows - Chatterjee, Krishnendu; Doyen, Laurent; Randour, Mickael; Raskin, Jean
We consider two-player games played on weighted directed graphs with mean-payoff and total-payoff objectives, two classical quantitative objectives. While for single-dimensional games the complexity and memory bounds for both objectives coincide, we show that in contrast to multi-dimensional mean-payoff games that are known to be coNP-complete, multi-dimensional total-payoff games are undecidable. We introduce conservative approximations of these objectives, where the payoff is considered over a local finite window sliding along a play, instead of the whole play. For single dimension, we show that (i) if the window size is polynomial, deciding the winner takes polynomial time, and (ii) the existence of a bounded window can be decided in NP ∩ coNP, and is at least as hard as solving mean-payoff games. For multiple dimensions, we show that (i) the problem with fixed window size is EXPTIME-complete, and (ii) there is no primitive-recursive algorithm to decide the existence of a bounded window.

Packing ellipsoids with overlap - Uhler, Caroline; Wright, Stephen (SIAM Review)
The problem of packing ellipsoids of different sizes and shapes into an ellipsoidal container so as to minimize a measure of overlap between ellipsoids is considered. A bilevel optimization formulation is given, together with an algorithm for the general case and a simpler algorithm for the special case in which all ellipsoids are in fact spheres. Convergence results are proved and computational experience is described and illustrated. The motivating application-chromosome organization in the human cell nucleus-is discussed briefly, and some illustrative results are presented.

Tension-oriented cell divisions limit anisotropic tissue tension in epithelial spreading during zebrafish epiboly - Campinho, Pedro; Behrndt, Martin; Ranft, Jonas; Risler, Thomas; Minc, Nicolas; Heisenberg, Carl-Philipp J (Nature Cell Biology)
Epithelial spreading is a common and fundamental aspect of various developmental and disease-related processes such as epithelial closure and wound healing. A key challenge for epithelial tissues undergoing spreading is to increase their surface area without disrupting epithelial integrity. Here we show that orienting cell divisions by tension constitutes an efficient mechanism by which the enveloping cell layer (EVL) releases anisotropic tension while undergoing spreading during zebrafish epiboly. The control of EVL cell-division orientation by tension involves cell elongation and requires myosin II activity to align the mitotic spindle with the main tension axis. We also found that in the absence of tension-oriented cell divisions and in the presence of increased tissue tension, EVL cells undergo ectopic fusions, suggesting that the reduction of tension anisotropy by oriented cell divisions is required to prevent EVL cells from fusing. We conclude that cell-division orientation by tension constitutes a key mechanism for limiting tension anisotropy and thus promoting tissue spreading during EVL epiboly.

Pupal cocoons affect sanitary brood care and limit fungal infections in ant colonies - Tragust, Simon; Ugelvig, Line V; Chapuisat, Michel; Heinze, Jürgen; Cremer, Sylvia (BMC Evolutionary Biology)
Background: The brood of ants and other social insects is highly susceptible to pathogens, particularly those that penetrate the soft larval and pupal cuticle. We here test whether the presence of a pupal cocoon, which occurs in some ant species but not in others, affects the sanitary brood care and fungal infection patterns after exposure to the entomopathogenic fungus Metarhizium brunneum. We use a) a comparative approach analysing four species with either naked or cocooned pupae and b) a within-species analysis of a single ant species, in which both pupal types co-exist in the same colony. Results: We found that the presence of a cocoon did not compromise fungal pathogen detection by the ants and that species with cocooned pupae increased brood grooming after pathogen exposure. All tested ant species further removed brood from their nests, which was predominantly expressed towards larvae and naked pupae treated with the live fungal pathogen. In contrast, cocooned pupae exposed to live fungus were not removed at higher rates than cocooned pupae exposed to dead fungus or a sham control. Consistent with this, exposure to the live fungus caused high numbers of infections and fungal outgrowth in larvae and naked pupae, but not in cocooned pupae. Moreover, the ants consistently removed the brood prior to fungal outgrowth, ensuring a clean brood chamber. Conclusion: Our study suggests that the pupal cocoon has a protective effect against fungal infection, causing an adaptive change in sanitary behaviours by the ants. It further demonstrates that brood removal-originally described for honeybees as "hygienic behaviour"-is a widespread sanitary behaviour in ants, which likely has important implications on disease dynamics in social insect colonies.

The force and effect of cell proliferation - Campinho, Pedro; Heisenberg, Carl-Philipp J (EMBO Journal)
The spatiotemporal control of cell divisions is a key factor in epithelial morphogenesis and patterning. Mao et al (2013) now describe how differential rates of proliferation within the Drosophila wing disc epithelium give rise to anisotropic tissue tension in peripheral/proximal regions of the disc. Such global tissue tension anisotropy in turn determines the orientation of cell divisions by controlling epithelial cell elongation.

The influence of demography and local mating environment on sex ratios in a wind-pollinated dioecious plant - Pickup, Melinda; Barrett, Spencer (Ecology and Evolution)
Negative frequency-dependent selection should result in equal sex ratios in large populations of dioecious flowering plants, but deviations from equality are commonly reported. A variety of ecological and genetic factors can explain biased sex ratios, although the mechanisms involved are not well understood. Most dioecious species are long-lived and/or clonal complicating efforts to identify stages during the life cycle when biases develop. We investigated the demographic correlates of sex-ratio variation in two chromosome races of Rumex hastatulus, an annual, wind-pollinated colonizer of open habitats from the southern USA. We examined sex ratios in 46 populations and evaluated the hypothesis that the proximity of males in the local mating environment, through its influence on gametophytic selection, is the primary cause of female-biased sex ratios. Female-biased sex ratios characterized most populations of R. hastatulus (mean sex ratio = 0.62), with significant female bias in 89% of populations. Large, high-density populations had the highest proportion of females, whereas smaller, low-density populations had sex ratios closer to equality. Progeny sex ratios were more female biased when males were in closer proximity to females, a result consistent with the gametophytic selection hypothesis. Our results suggest that interactions between demographic and genetic factors are probably the main cause of female-biased sex ratios in R. hastatulus. The annual life cycle of this species may limit the scope for selection against males and may account for the weaker degree of bias in comparison with perennial Rumex species.

Quantitative reactive modeling and verification - Henzinger, Thomas A (Computer Science Research and Development)
Formal verification aims to improve the quality of software by detecting errors before they do harm. At the basis of formal verification is the logical notion of correctness, which purports to capture whether or not a program behaves as desired. We suggest that the boolean partition of software into correct and incorrect programs falls short of the practical need to assess the behavior of software in a more nuanced fashion against multiple criteria. We therefore propose to introduce quantitative fitness measures for programs, specifically for measuring the function, performance, and robustness of reactive programs such as concurrent processes. This article describes the goals of the ERC Advanced Investigator Project QUAREM. The project aims to build and evaluate a theory of quantitative fitness measures for reactive models. Such a theory must strive to obtain quantitative generalizations of the paradigms that have been success stories in qualitative reactive modeling, such as compositionality, property-preserving abstraction and abstraction refinement, model checking, and synthesis. The theory will be evaluated not only in the context of software and hardware engineering, but also in the context of systems biology. In particular, we will use the quantitative reactive models and fitness measures developed in this project for testing hypotheses about the mechanisms behind data from biological experiments.

ECHIDNA mediated post Golgi trafficking of auxin carriers for differential cell elongation - Boutté, Yohann; Jonsson, Kristoffer; Mcfarlane, Heather; Johnson, Errin; Gendre, Delphine; Swarup, Ranjan; Friml, Jirí; Samuels, Lacey; Robert, Stéphanie; Bhalerao, Rishikesh (PNAS)
The plant hormone indole-acetic acid (auxin) is essential for many aspects of plant development. Auxin-mediated growth regulation typically involves the establishment of an auxin concentration gradient mediated by polarly localized auxin transporters. The localization of auxin carriers and their amount at the plasma membrane are controlled by membrane trafficking processes such as secretion, endocytosis, and recycling. In contrast to endocytosis or recycling, how the secretory pathway mediates the localization of auxin carriers is not well understood. In this study we have used the differential cell elongation process during apical hook development to elucidate the mechanisms underlying the post-Golgi trafficking of auxin carriers in Arabidopsis. We show that differential cell elongation during apical hook development is defective in Arabidopsis mutant echidna (ech). ECH protein is required for the trans-Golgi network (TGN)-mediated trafficking of the auxin influx carrier AUX1 to the plasma membrane. In contrast, ech mutation only marginally perturbs the trafficking of the highly related auxin influx carrier LIKE-AUX1-3 or the auxin efflux carrier PIN-FORMED-3, both also involved in hook development. Electron tomography reveals that the trafficking defects in ech mutant are associated with the perturbation of secretory vesicle genesis from the TGN. Our results identify differential mechanisms for the post-Golgi trafficking of de novo-synthesized auxin carriers to plasma membrane from the TGN and reveal how trafficking of auxin influx carriers mediates the control of differential cell elongation in apical hook development.

Cryptographically enforced RBAC - Ferrara, Anna; Fuchsbauer, Georg; Warinschi, Bogdan
Cryptographic access control promises to offer easily distributed trust and broader applicability, while reducing reliance on low-level online monitors. Traditional implementations of cryptographic access control rely on simple cryptographic primitives whereas recent endeavors employ primitives with richer functionality and security guarantees. Worryingly, few of the existing cryptographic access-control schemes come with precise guarantees, the gap between the policy specification and the implementation being analyzed only informally, if at all. In this paper we begin addressing this shortcoming. Unlike prior work that targeted ad-hoc policy specification, we look at the well-established Role-Based Access Control (RBAC) model, as used in a typical file system. In short, we provide a precise syntax for a computational version of RBAC, offer rigorous definitions for cryptographic policy enforcement of a large class of RBAC security policies, and demonstrate that an implementation based on attribute-based encryption meets our security notions. We view our main contribution as being at the conceptual level. Although we work with RBAC for concreteness, our general methodology could guide future research for uses of cryptography in other access-control models.